Adaptive Learning for Improving German-Speaking Skills in the Digital Age - Sudarmaji Sudarmaji; Aditya Rikfanto (Makassar State University, 2022)
Abstract. Language teaching has developed with the support of techniques, media, and learning approaches that complement each other. However, the need to develop linguistic skills never arrest and need to be improved continuously. One of the models developed in the early 21st century is adaptive learning, but this learning tends to be more widely applied outside of language teaching. Therefore, This study aims to find concrete forms of adaptive learning that can be applied in appropriately developing speaking skills in German. A qualitative, descriptive approach is employed in this study, focusing on an inductive inquiry into phenomena and fact-finding on adaptive learning. The learning source employed in the learning is a coursebook called Netzwerk Deutsch als Fremdsprache.To bridge the rigidity of the content and the less flexible learning aspects delivered by the coursebook, we tried to integrate it with the campus internal learning management system Besmart-Moodle. There were 12 students (initials P1-12) who participated in learning and practising speaking-oriented learning. We collected data using video recordings, digital questionnaires and field notes. Afterwards, we analyzed participants' conduct and responses using coding procedures to formulate categories relevant to adaptive learning forms. The results showed that most participants viewed this learning positively, and it supported improving their speaking skills effectively. In addition, for both students and lecturers, this learning model thoroughly impacted the learning process concerning certain linguistic facets and enriched previous research.Keywords: Adaptive learning, German, Speaking Skills, Digital Learning, Besmart